Gender, violence, refugees - Buckley-Zistel, Susanne; Krause, Ulrike (Studies in forced migration, 2019)
Providing nuanced accounts of how the social identities of men and women, the context of displacement and the experience or manifestation of violence interact, this collection offers conceptual analyses and in-depth case studies to illustrate how gender relations are affected by displacement, encampment and return. The essays show how these factors lead to various forms of direct, indirect and structural violence. This ranges from discussions of norms reflected in policy documents and practise, the relationship between relief structures and living conditions in camps, to forced military recruitment and forced return, and covers countries in Africa, Asia and Europe.